Risk Factors Affecting Stunting in the First 1.000 Days of Life in Indonesia: A Systematic Review - Salma, Erlinda Rasikhah Hadi; Qomaruddin, Mochammad Bagus; Devy, Shrimarti Rukmini (Jurnal Ilmiah Permas: Jurnal Ilmiah STIKES Kendal, 2024)
One of aims SDGs is Zero Hunger to reduce the number of children who suffer from stunting to ensure a healthy life and improve well-being. We intend to evaluate the current literature published from 2018 to 2023 which study the influence factors stunting in the first 1000 days of life in Indonesia. Aims : The research was to systematically review risk factor that contribute stunting in Indonesia. Methods: this study applied a systematic review using meta-analysis (PRISMA) with some inclusion criteria compiled in three database from PubMed, ProQuest, and ScienceDirect. Results: A total of 10 selected articles show that risk factors affecting stunting in Indonesia such as maternal education and knowledge, parenting style, family income, dietary habit, and sanitation.. Conclusion: The systematic review's findings that risk factor of stunting such as low maternal education and knowledge, low parenting, poor sanitation, low family income were factors most frequently linked to stunting in children. By empowering the local community to make proper weaning food and meets the required nutritional content, an approach that offers continuous guidance and intensive socialization about improving nutritional status so can help to prevent stunting in children.